2018
DOI: 10.1055/a-0597-8948
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TIGIT and FCRL3 is Altered in T Cells from Patients with Distinct Patterns of Chronic Autoimmune Thyroiditis

Abstract: Multiple IR, namely FCRL3 and TIGIT, but not the transcription factors HELIOS and FOXP3E2, showed increased mRNA levels in PB T cells from end-stage, long-standing and/or more aggressive AT, in proportion to disease severity. A relation with major clinical subphenotypes was observed, thereby identifying IR as potentially important players in AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As existing research have confirmed that abnormalities in function or number of Tregs are a feature of autoimmune diseases, to date, numerous animal models and human studies have verified the upregulation of TIGIT + Tregs in various autoimmune diseases, such as NOD mouse islets, type1 diabetes (T1D) patients, 92,93 thyroiditis, 94,95 aplastic anemia (AA), 96 multiple sclerosis (MS) 97 and noninfectious uveitis, 98 and may be proportional to disease severity.…”
Section: Tigit Expression In Autoimmune Diseasesmentioning
confidence: 99%
“…As existing research have confirmed that abnormalities in function or number of Tregs are a feature of autoimmune diseases, to date, numerous animal models and human studies have verified the upregulation of TIGIT + Tregs in various autoimmune diseases, such as NOD mouse islets, type1 diabetes (T1D) patients, 92,93 thyroiditis, 94,95 aplastic anemia (AA), 96 multiple sclerosis (MS) 97 and noninfectious uveitis, 98 and may be proportional to disease severity.…”
Section: Tigit Expression In Autoimmune Diseasesmentioning
confidence: 99%
“…cDNA Synthesis and RT-qPCR Experiments cDNA synthesis was accomplished with the PrimeScript ™ RT Reagent kit (Takara Bio, USA) using 100 ng of total RNA input in a 40 ml final mastermix reaction, as previously described (39) Quantity and purity of RNA samples were initially verified by OD 260 /OD 280 ratio > 1.8. using IMPLEN NanoPhotometer P-Class P-330 (IMPLEN GmbH, Germany). Obtained cDNA samples were diluted 6-fold and used as a template for subsequent quantitative real-time PCR analysis of eight selected targets (PLZF/ZBTB16, RUNX3, RORC, TBX21, EOMES, IL-18R, CCR6, CCR10) and two reference genes (ACTB and TBP) using QuantStudio 5 instrument (Thermo Fisher Scientific, USA).…”
Section: Flow Cytometry Analysis Of Peripheral Mr1-restricted and Gdtmentioning
confidence: 99%